2000
DOI: 10.1161/01.cir.101.12.1358
|View full text |Cite
|
Sign up to set email alerts
|

L-NMMA (a Nitric Oxide Synthase Inhibitor) is Effective in the Treatment of Cardiogenic Shock

Abstract: L-NMMA administration in patients with cardiogenic shock is safe and has favorable clinical and hemodynamic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 7 publications
2
60
0
1
Order By: Relevance
“…53 Indeed, preliminary studies in patients with refractory cardiogenic shock have shown improved hemodynamic status and survival with N G -monomethyl-L-arginine, a nitric oxide synthase inhibitor. 54 Considering their likely role in plaque destabilization and in vascular and myocardial remodeling, MMPs represent another potential therapeutic target. Inhibitors of MMPs are currently being investigated in acute MI, although it is unlikely that chronic, broad-spectrum MMP inhibitors will have a favorable tolerability profile.…”
Section: Treatment Of the Acs: Perspective On The Futurementioning
confidence: 99%
“…53 Indeed, preliminary studies in patients with refractory cardiogenic shock have shown improved hemodynamic status and survival with N G -monomethyl-L-arginine, a nitric oxide synthase inhibitor. 54 Considering their likely role in plaque destabilization and in vascular and myocardial remodeling, MMPs represent another potential therapeutic target. Inhibitors of MMPs are currently being investigated in acute MI, although it is unlikely that chronic, broad-spectrum MMP inhibitors will have a favorable tolerability profile.…”
Section: Treatment Of the Acs: Perspective On The Futurementioning
confidence: 99%
“…11 Some preliminary clinical studies suggest that these hemodynamic effects may increase survival and decrease the need for support with intra-aortic balloon pumps and mechanical ventilation. 4,12,13 Despite evidence that NOS and NO play a role in CS, little is known about the levels of the NOS substrate arginine and its metabolites. Arginine availability may limit NO synthesis, particularly in cells expressing iNOS.…”
Section: Clinical Perspective P 2324mentioning
confidence: 99%
“…Pathophysiological observations and hemodynamic end-point studies suggested that a novel nitric oxide synthase Dauerman Death, Shock, and Aortic Stenosis 1443 inhibitor, tilarginine, would clearly be superior to standard therapy for patients with acute myocardial infarction complicated by cardiogenic shock. 8 When an international, multicenter, mortality-driven trial was performed, the surrogate end points proved useless, and tilarginine had no effect on mortality. 9 Similarly, the superiority of TAVR seems clear retrospectively, but the benefit was much less clear to patients and investigators during the trial.…”
Section: Interventional Cardiology Trials and Deathmentioning
confidence: 99%